2019
DOI: 10.5469/neuroint.2019.00115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long Term Prognosis between Carotid Endarterectomy versus Stenting; A Korean Population-Based Study Using National Insurance Data

Abstract: Although carotid endarterectomy (CEA) is recommended as a treatment for carotid stenosis rather than carotid artery stenting (CAS), CAS has been preferred in Korea. The aim of this study was to analyze long-term outcomes after CAS compared with CEA using Korean nationwide insurance data. Materials and Methods: We obtained all data from the nationwide database of the Health Insurance Review & Assessment Service (HIRA) during the study period using several codes regarding the procedure or operation. We included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Stent technology has been gradually widely developed in recent years, and the upgrading of materials, technologies and concepts has reduced the complications to an acceptable range. New clinical trials have shown that CEA and CAS have no signi cant difference in the incidence of surgical complications and long-term prognosis of patients [35][36][37][38][39], and more clinical trials are needed in the later stage to support the more widespread application of stent technology, in order to further explore the surgical indications of these two [40].…”
Section: Discussionmentioning
confidence: 99%
“…Stent technology has been gradually widely developed in recent years, and the upgrading of materials, technologies and concepts has reduced the complications to an acceptable range. New clinical trials have shown that CEA and CAS have no signi cant difference in the incidence of surgical complications and long-term prognosis of patients [35][36][37][38][39], and more clinical trials are needed in the later stage to support the more widespread application of stent technology, in order to further explore the surgical indications of these two [40].…”
Section: Discussionmentioning
confidence: 99%
“… 15 In a study conducted in Korea, fewer ischemic strokes were observed in patients with dyslipidemia. 16 Regarding the cholesterol profile, LDL-C levels are related to new diffusion-weighted image lesions observed in the acute phase immediately after CAS. 17 However, a long-term follow-up study demonstrated that low HDL-C level was an independent predictor of stroke, MI, and all-cause mortality after CAS, whereas LDL-C level was not.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,7 Third, although CEA was principally recommended for revascularization of asymptomatic carotid stenosis, CAS has now been performed more frequently than CEA in some countries. 8 At this point, understanding the available evidence on revascularization treatment, especially focusing on CAS, can be helpful in setting up an optimal treatment strategy for asymptomatic carotid stenosis. Thus, this review aimed to pragmatically organize the information that is necessary for a clinical decision on CAS in asymptomatic carotid stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Such an improvement might result in attenuating the relative efficacy of revascularization treatment in asymptomatic carotid stenosis [ 3 , 6 , 7 ]. Third, although CEA was principally recommended for revascularization of asymptomatic carotid stenosis, CAS has now been performed more frequently than CEA in some countries [ 8 ].…”
Section: Introductionmentioning
confidence: 99%